Did the intensity of countries’ digital transformation affect IT companies’ performance during covid-19? - El Khoury, Rim (2022)
This study explores the impact of the intensity of countries’ digital transformation on the performance of 3961 global companies in the Information Technology sector in 2020. We analyse the impact of e-government index, e-participation index, and cybersecurity commitment on firms’ performance (enterprise value, book value per share, and cash flow from operation per share) using OLS regression. A structural equation modelling was further employed to explain the mediating role of cybersecurity commitment. Results suggest that e-government has a positive linkage with cybersecurity commitment and performance. However, there is preliminary evidence that cybersecurity measures initiated by e-government will drive performance. The e-participation index has a positive association with cybersecurity commitment and a heterogeneous impact on performance, suggesting the need to differentiate between development and participation. Finally, results highlight the pivotal role of e-government and cybersecurity commitment in boosting the profitability of companies and supporting the influence of the surrounding technological environment on companies’ performance.